Pengaruh Penggunaan Media Video Pembelajaran Materi Aku Anak Shaleh Terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI Kelas V SDN 07 Sungai Sariak - Qamari, Dinda Najmi; Yusri, Meldi Ade Kurnia; Eldarni, Eldarni; Pratiwi, Rahmi (Indo-MathEdu Intellectuals Journal, 2025)
This research started from the problems found in the field, namely low student learning outcomes, which was caused by the lack of use of learning media that supported the student learning process. The learning approach used by teachers is less varied and does not utilize digital media, so that students have difficulty understanding the material. This study uses a quantitative research method with a quasi-experimental form. The population of this study is class V students at SDN 07 Sungai Sariak which totals 50 students. Sampling uses the total sampling technique, namely the entire population is used as a sample, namely the VA class as the experimental class and the VB class as the control class. The data collection technique uses a multiple-choice test. The data analysis in this study uses a t-test. The results of the data analysis obtained an average value of 86 for the experimental group, higher than the average value of the control group of 75.8. From the analysis of the t-test, tcal>ttable=2.704>2.010 was obtained. This means that there is a significant difference in learning outcome scores at the α level of 0.05. Therefore, it can be concluded that the use of learning video media has an effect on the learning outcomes of PAI students in grade V at SDN 07 Sungai Sariak, Padang Pariaman Regency